Development of a Physical Fitness Activity Movement Quality Test Instrument - Terbit Surya; Citra Resita; Resty Gustiawati (STKIP Muhammadiyah Kuningan, 2023)
This study aims to produce a test instrument for the quality of motion for physical fitness activities and to determine the feasibility of a test instrument for the quality of movement for physical fitness activities in junior high school students. This type of research is research and development (research & development) of the Borg and Gall model, which is simplified by Puslitjaknov involving five steps, namely: 1) analysis of the product being developed, 2) product development, 3) expert validation and revision, 4) group trials small scale and revision, 5) final product. The results of the research are in the form of a test instrument for the quality of movement for physical fitness activities, suitable for use and has been validated by experts for valid and reliable criteria, where the validity criteria are high, namely 0.80, with moderate expert consistency, namely 0.562, and based on the results of product trials of motion quality test instruments obtained valid and reliable criteria, where the results of the product Cobe test received an average value of r count 0.78 > 0.70, the validity was classified as high, and the reliability test received a score of 0.943 from 12 students the data is valid thus the instrument is in the high criteria. So the resulting motion quality test instrument is suitable for a learning evaluation tool on physical fitness activity material.